Gender Dynamics in Sorrows of Sarasvati: A Corpus-Based Transitivity Analysis - Ishaq, Samina; Choudhary, Aisha Zulfiqar; Din, Ghulam Muhei ud (Pakistan Languages and Humanities Review, 2025)
The present study aimed to analyze transitivity patterns in the novel Sorrows of Sarasvati. The purpose of the study was to analyze how certain meanings were being construed through the use of particular transitivity patterns. By doing so, the study planned to explicate the representation of characters of both the genders, male and female, by the author. The study is mixed method in nature. For the purpose of analysis, four characters, two male and two female, were selected. The total of 120 dialogues, 30 from each character, was purposively selected as sample data for the analysis. The corpus of the data was compiled in text form. Drawing on Halliday's (1985) transitivity model, scheme for the analysis was prepared, and the transitivity patterns were manually tagged in UAM corpus tool. The frequencies of the components of the transitivity were calculated overall as well as for each character. Further, the frequencies across male and female characters were compared. The results revealed a complex nature of character construal for the gender. The findings suggest that female characters were observed to be using more mental, relational, and material processes signifying that the characters were a mix of stereotypical and independent personas. Interestingly, the transitivity patterns used by male characters seemed to defy the typical strong, courageous, careless, and independent image of masculinity. The study is helpful for the academicians, both teachers and students, and researchers interested in the field to explore patterns of transitivity along with portrayal of both male and female gender.